Aku (Bukan) Preman - , IKE ASTRININGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research elaborates on the impact ofaweak stateinpowermanagementatthe village levelwhich raises theeverydaymaker. Everyday makeris a non-government entity which have power to make policy. They take over stateâs particular roles in creating rules in the form ofnorms.They become âthe guard normâitself, without any resistance from the village government, religious leaders, and other groups about how the norms is defined. The norms are aboutthe curfew at 11 pm and the ban of bringing guests without permission from the neighbourhood leader. In performing the role of guarding thenorm, everyday makerin Langon Village, Ponggok, Blitar rely on the power of mass. They catch the norm violators by inviting their group, around 20-30 members. They require payment of fines in form of money. The amount of the money is adjusted, depend on who isthe violators and what kind of violation they did. Everyday makertake over the role of the state in determining rules and the punishment. The norms from the everyday maker become hegemonic and rule out the standard normsin society. The standard norms are drunk, narcotics addiction, stealing, cheating/having affair,gambling, or mendem, madat, maling, medok, main (molimo). Everyday makeris known as new norms former and the guard norm, but also other norm violators. In that case, the emergence of everyday makerin society shows small practices of shadow state and effort of re-religious-ization the village. The practices of shadow states is shown with the taking over the stateâs rule as a former and guard of the norms by everyday maker. They are grassroots but become important actor in villageâs political landscape. The process of re-religious-ization of the village is on 2003-2010. Before 2003, if they were norm violators such as cohabiting, there is no punishment because noone paid attention to it. The 7 th years existence of everyday maker, social norms as curfew and banning of bringing guests without neighbourhood leader permission become importantand hegemonic rules in society